Prediction of metastatic prostate cancer by prostate-specific antigen in combination with T stage and Gleason Grade: Nationwide, population-based register study - Thomsen, Frederik B. (PLoS One, 2020)
The objective was to investigate the proportion of men with metastatic prostate cancer in groups defined by T stage, Gleason Grade Group (GGG) and serum levels of prostate-specific antigen (PSA) and if PSA can be used to rule in metastatic prostate cancer when combined with T stage and GGG. We identified 102,076 men in Prostate Cancer data Base Sweden 4.0 who were diagnosed with prostate cancer in 2006–2016. Risk of metastases was assessed for PSA stratified on T stage and five-tiered GGG. For men who had not undergone bone imaging, we used multiple imputation to classify metastatic prostate cancer. Advanced T stage, high GGG and high PSA were related to bone metastases. For example: only 79/38 190 (0.2%) of men with T1-2 and GGG 1 had PSA above 500 ng/mL, and 29/79 (44%) of these men had metastases; whereas 1 154/7 018 (16%) of men with T3-4 and GGG 5 had PSA above 500 ng/ml and 1 088/1 154 (94%) of these men had metastases. However, no PSA cut-off could accurately identify the majority of men with metastatic prostate cancer (i.e. high sensitivity) while also correctly classifying most men without metastasis (i.e. high specificity). In conclusion, these results support the use of imaging to confirm bone metastases in men with advanced prostate cancer as no PSA level in combination with T stage and GGG could accurately rule in metastatic prostate cancer and thereby safely omit bone imaging.